Students' conceptual change on factors affecting rate of chemical reactions - Jonson, Lorna N. (Animo Repository, 2004)
This study focused on the students conceptual change on factors affecting rate of chemical reactions using the three-stage conceptual change-teaching model in the lecture and the structured inquiry approach in the laboratory. It determined the students pre-instructional conceptions and students post-instructional conceptions on rate of reaction and factors affecting rate of chemical reactions. It also determined the students level of understanding on rate of reaction and factors affecting rate of chemical reactions prior to and after instruction. Finally, it determined the changes in the conceptions of the students on the concepts. This study involved one intact class of fifteen (15) education students major in home economics enrolled in chemistry 112 in the second semester of SY 2003-2004 at the University of Eastern Philippines, Catarman, Northern Samar and it was conducted for three weeks. A 10-item multiple choice test with open-ended part, focus group discourse (FGD), laboratory group reports, conceptual trace analysis, and unstructured post interview to verify answers to the posttest, were utilized to gather the data. The data were analyzed using the conceptual trace analysis of Jensen and Finley (1995) as modified by Ferido (1999). The findings of the study revealed that 66.67% of the students pre-instructional conceptions were scientifically incomplete or incorrect ideas and 33.33% were correct ideas on factors affecting rate of chemical reactions. But after instruction, 61.54% of the students ideas were incorrect/incomplete and 38.46% were correct. There was a decrease in the percentage of the ideas, which were incorrect/incomplete, and there was an increase in the percentage of the ideas, which were correct after instruction. The students levels of conceptual understanding prior to instruction were mostly on the worst understanding (WU) and partial understanding (PU) categories. After instruction, their levels of understanding were mostly best understand.